Activation of SAPK/JNK mediated the inhibition and reciprocal interaction of DNA methyltransferase 1 and EZH2 by ursolic acid in human lung cancer cells - Wu, Jingjing (J Exp Clin Cancer Res, 2015)
BACKGROUND: Ursolic acid (UA), a pentacyclic triterpenoid, is known to have anti-tumor activity in various cancers including human non small cell lung cancer (NSCLC). However, the molecular mechanisms underlying the action of UA remain largely unknown. METHODS: Cell viability was measured by MTT assays. Apoptosis was analyzed with Annexin V-FITC/PI Apoptosis Detection Kit by Flow cytometry. Western blot analysis was performed to measure the phosphorylation and protein expression of stress-activated protein kinase/c-Jun N-terminal kinase (SAPK/JNK), DNMT1 [DNA (cytosine-5)-methyltransferase 1], enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2) and SP1. Exogenous expression of SP1 and DNMT1 was carried out by transient transfection assays. RESULTS: We showed that UA inhibited the growth and induced apoptosis of NSCLC cells in the dose- and time-dependent fashion. Furthermore, we found that UA induced phosphorylation of SAPK/JNK and suppressed the protein expression of DNMT1 and EZH2. The inhibitor of SAPK/JNK (SP600125) blocked the UA-reduced expression of DNMT1 and EZH2. In addition, UA suppressed the expression of SP1 protein. Conversely, overexpression of SP1 reversed the effect of UA on DNMT1 and EZH2 expression, and feedback attenuated UA-induced phosphorylation of SAPK/JNK. Moreover, exogenous expression of DNMT1 antagonized the effect of UA on SAPK/JNK signaling, EZH2 protein expression, and NSCLC cell growth. CONCLUSION: Our results show that UA inhibits growth of NSCLC cells through SAPK/JNK-mediated inhibition of SP1; this in turn results in inhibition the expression of DNMT1 and EZH2. Overexpression of DNMT1 diminishes UA-reduced EZH2 protein expression. The negative feedback regulation of SAPK/JNK signaling by SP1 and DNMT1, and the reciprocal interaction of EZH2 and DNMT1 contribute to the overall effects of UA. This study leads to important new insights into the mechanisms by which UA controls growth of NSCLC cells.